Perbandingan Kapasitas Pemerintah Daerah dalam Mengelola Dana Otonomi Khusus di Aceh dan Papua - Ahya Riwanda Muharram; Furqan Al Fatin; Dwi Nurazalia; Nurul Kamaly; Zakirah Azman (Journal of Literature Review, 2026)
Special autonomy in Aceh and Papua was granted to mitigate conflict and accelerate prosperity through substantial authority and funding. However, after two decades, its impact remains debated and has not been evenly felt by the community. The purpose of this study is to analyze differences in local government capacity in managing special autonomy funds and the indicators that influence their effectiveness. The method used in this study was library research, using sources such as journal articles, regulations, planning documents, and audit reports from the Supreme Audit Agency of the Republic of Indonesia in Aceh and Papua. The research "informants" were documents and literature. The results of the study indicate that the main obstacle is not the amount of funds, but the quality of governance at the regional level. Aceh is relatively strong in planning and regulation, but weak in coordination of implementation and oversight. Papua faces greater challenges in technical aspects of administration and reporting. These differences indicate that the effectiveness of special autonomy funds is largely determined by the institutional capacity of local governments to manage budgets accountably and transparently.